Airway Management in the Emergency Department During Coronavirus Disease (COVID-19) - Pothiawala, Sohil (Acta medica Lituanica, 2020)
Front-line health-care workers in the Emergency Department (ED) are at an increased risk of infection during the airway management of patients with known or suspected Emerging Viral Diseases (EVD) like Coronavirus Disease 2019 (COVID-19). The primary route for transmission of the virus from an infected patient to the ED staff is due to aerosolized droplets, and the transmission risk is high despite wearing adequate Personal Protective Equipment (PPE). There are limited evidence-based guidelines for airway management during these viral infections, especially with a focus on the principles of airway management in a busy, fast-paced ED. This article provides an overview of the principles of airway management in suspected or confirmed EVD patients, including COVID-19, particularly in the context of ED, and also considering strategies in resource limited setting. These principles should be adapted to suit your local department and hospital policy on airway management as well as national guidelines.